Psychometric properities of the Polish version of clinical learning environment inventory - Iwona Bodys-Cupak (BMC, 2021)
Abstract Background Clinical experience is a crucial activity for nursing students. The way students` perceive clinical placement exerts an immense influence on the learning process. This study aims to test the psychometric properties of a 19-item version of the Clinical Learning Environment Inventory under Polish clinical conditions. Method For this study, Discriminant validity and Cronbach's alpha reliabilities were computed. In order to measure content validity, the criterion validity Generalized Self Efficacy Scale and the Life Orientation Test - Revised were used. Results Cronbach's Alpha for the Clinical Facilitator Support of Learning Scale and the Satisfaction with Clinical Placement scale is 0.949 and 0.901, respectively. The Spearman's rank correlation coefficient indicates the existence of a positive correlation between the students' satisfaction with clinical placement and their [overall] life optimism. Age correlates negatively with perceived teacher support and positively with satisfaction with clinical placement. The sense of self-efficacy correlates negatively with their satisfaction with clinical placement. Clinical Learning Environment Inventory − 19 could be a useful tool to evaluate the quality of the clinical learning process in Polish conditions.